Pop-Up Special Section Introduction: Advertising and COVID-19—Examining the Impacts of the Pandemic on Agencies, Consumers, and Brands. Issue 3 (21st July 2021) - Bright, Laura F.; Schau, Hope Jensen
Abstract: The COVID-19 pandemic has made substantial impacts on every aspect of our lives, including our consumption habits and how we interact with communication messages like advertising. This special section examines the effects of the coronavirus pandemic on consumers, brands, stakeholders, and advertisers using a variety of theories and methodologies including experimental designs, text analysis, and content analysis. The research presented is divided into three key areas: (1) advertising's impact on society, (2) consumer behavior in a pandemic, and (3) pandemic message framing. These themes illustrate how consumers, brands, advertisers, and other stakeholders have proven to be resilient and compassionate in the face of an uncertain future.